“Tia, deixa eu escrever!”: os usos da linguagem escrita por crianças pequenas no cotidiano de um centro de educação infantil do município de Fortaleza - Mesquita, Elizangela Silva (2024)
The work presents the existence of a conjuncture of teacher and primary school of the 19th-20th centuries corresponding to the north-eastern region, in the Brazilian educational scenario. This conjuncture is formed by the constitution of "literary images", identified by means of a readability resource used for the systematic investigation of the main source, the literary work "Infância" (1945) by Graciliano Ramos (1892 - 1953). The analyses were carried out from a hermeneutic perspective with a theoretical foundation anchored in the ideas of Paul Ricoeur (1913-2005), and supported by epistemological instruments related to the theoretical positioning of historical studies based on Cultural History and its perspectives, crossed by the proposals of Jacques Le Goff (1990), in the New History; Roger Chartier (2002), in the New Cultural History; and Carlo Guinzburg (1989), in Microhistory. The methodological approach to the source, in addition to using the bibliographical method, was guided by the historical method in convergence with the evolution of knowledge in the historiographical aspect, which occurred by the way the question is addressed, according to Luca (2020). The survey and historical critique of the data were scrutinised using comparative criteria with the educational proposals of the European pedagogues Johann Pestalozzi (1746-1827) and Friedich Froebel (1782-1852). The constitution of the literary images revealed an educational scenario of the 19th-20th centuries, both in its contributions that provoked criticism and reflection, and in the development of interpretations with historical-educational backing and new questions and elucidations regarding the field of History and Memory of Education.